2021
DOI: 10.3390/ijms22147692
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Diet and Exercise on Drug Responses

Abstract: It is well known that lifestyle changes can alter several physiological functions in the human body. For exercise and diet, these effects are used sensibly in basic therapies, as in cardiovascular diseases. However, the physiological changes induced by exercise and a modified diet also have the capacity to influence the efficacy and toxicity of several drugs, mainly by affecting different pharmacokinetic mechanisms. This pharmacological plasticity is not clinically relevant in all cases but might play an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 178 publications
(196 reference statements)
0
19
0
1
Order By: Relevance
“…3,20 Those inhibitory effects can be further amplified by dietary habits, lifestyle, and specific metabolism, accumulation, and elimination rates. 34 For instance, the accumulation and risk of adverse DDIs with toxic chemicals that occur in meat and dairy products might be lower than the average in vegan and vegetarian populations, but higher in communities that rely on them as primary food sources.…”
Section: Articlementioning
confidence: 99%
“…3,20 Those inhibitory effects can be further amplified by dietary habits, lifestyle, and specific metabolism, accumulation, and elimination rates. 34 For instance, the accumulation and risk of adverse DDIs with toxic chemicals that occur in meat and dairy products might be lower than the average in vegan and vegetarian populations, but higher in communities that rely on them as primary food sources.…”
Section: Articlementioning
confidence: 99%
“…The physiological consequences of exercise and diet include changes in drug efficacy and toxicity. 189 For instance, a recent metagenomic and transcriptomic study shows that recovery from a dysbiosis-inducing therapy (ie, antibiotics) is also very much dependent on dietary management. 190 Interestingly, just as the diet habits can affect gut health, the alteration of the microbiome may also affect eating habits which is linked with the SCFA metabolism.…”
Section: Dysbiosis and Cardiovascular Diseasesmentioning
confidence: 99%
“…"Several studies have shown that diet and body composition as well as exercise are lifestyle components that can influence many components of drug metabolism and efficacy. Patients are often not aware of the potential risk factors, which are particularly important if drugs with a narrow therapeutic range/window are used" [69]. "Physiological adaptations to acute and chronic exercise are such that there is good reason to suspect that exercise has the potential to significantly influence drug absorption and bioavailability, drug distribution within the body, and drug elimination from the body.…”
Section: Sino-nasalmentioning
confidence: 99%